2010
DOI: 10.4132/koreanjpathol.2010.44.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Tumors to the Breast from Extramammary Malignancies

Abstract: Background : Metastases to the breast from extramammary malignancies are very rare. We describe here the clinicopathologic features of the metastatic breast tumors that were identified in Korean patients at a single institute. Methods : We analyzed the clinicopathologic data of the patients who were diagnosed between January 1989 and April 2009 at Asan Medical Center. Results : Only 31 (0.21%) patients with metastases to the breast from extramammary malignancies were diagnosed over a 20-year period, and 29 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These figures may be underestimates, as some diagnoses may have been missed and some cases may not have been found in the search of the pathology computer. Five studies of patients largely diagnosed between 1990 and 2010 found incidences of between 0.2% and 0.5% 2,6–9 . We have not found any large studies since 2010.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…These figures may be underestimates, as some diagnoses may have been missed and some cases may not have been found in the search of the pathology computer. Five studies of patients largely diagnosed between 1990 and 2010 found incidences of between 0.2% and 0.5% 2,6–9 . We have not found any large studies since 2010.…”
Section: Discussionmentioning
confidence: 57%
“…Five studies of patients largely diagnosed between 1990 and 2010 found incidences of between 0.2% and 0.5%. 2,[6][7][8][9] We have not found any large studies since 2010. It not possible to be sure why the increase occurred in Nottingham.…”
Section: Discussionmentioning
confidence: 92%